A1166C POLYMORPHISM OF THE GENE FOR ANGIOTENSIN II RECEPTOR 1ST TYPE AND ENDOTHELIAL DYSFUNCTION IN MEN WITH A HISTORY OF MYOCARDIAL INFARCTION IN YOUNG AGE - O. A. Berkovich; E. A. Bazhenova; E. V. Volkova; M. Z. Alugishvili; N. V. Vahrameeva; I. O. Kiselev; E. V. Shlyahto; E. I. Schwarz (Российский кардиологический журнал, 2000)
The renin-angiotensin-aldosterone system (RAAS) is involved in the pathogenesis of Coronary Heart Disease and myocardial infarction. The crucial component of the RAAS is angiotensin II and its effects are carried out by angiotensin II receptors 1st type (AT1R).Aim of the study: determine the incidence of the mutant allele of the AT1R gene, estimate possible correlations between AT1R gene polymorphism and the extension of endothelial dysfunction in patients who have suffered MI in the age under 45.Materials and methods: 122 men suffering myocardial infarction under the age of 45 have been examined. In all patients we measured a relative increase of brachial artery diameter during the test with reactive hyperemia, the number of circulating endotheliocytes. Identification of A1166C polymorphism of the AT1R gene was carried out by means of polymerase chain reaction (PCR).Results: in patients with a history of myocardial infarction in the age under 45 we have found evidence of endothelial dysfunction: increased circulating endotheliocytes, decreased endothelium-mediated vasodilation. Among patients with a vasoconstrictive reaction the incidence of the C allele of the AT1R gene was higher than in patients exhibitng a vasodilative response during a test with reactive hyperemia (P<0.007). The incidence of the mutant allele of the AT1R gene was reliably lower in coronary patients with arterial hypertension than in those without hypertension.